Switching from intravenous to subcutaneous infliximab is safe and feasible in patients with perianal Crohn’s disease - Pauline Wils; Mathurin Fumery; Maria Nachury; Clara Yzet; Dilek Coban; Anthony Buisson (Therapeutic Advances in Gastroenterology)
Background and objectives: We assessed the evolution of perianal lesions after switching intravenous (IV) to subcutaneous (SC) infliximab in patients with Crohn’s disease (CD). Design: Subgroup analysis of REMSWITCH studies. Methods: We described the clinical and MRI outcomes of patients with a prior or current CD perianal lesions after the switch. Results: In REMSWITCH, 40 CD patients had a prior history of perianal lesions. No patient experienced a new perianal lesion (median follow-up = 18 months). Among the three patients (3/40, 7.5%) with clinically active perianal lesions at baseline, two patients had no more perianal lesions at month 18 while the last patient experienced lesions worsening. Another one with active perianal lesions on MRI but no symptom at baseline did not have any relapse within 18 months. Only one patient (1/40, 2.5%) had a perianal relapse (at month 25) with remission recapture after SC infliximab intensification. Conclusion: Switching from IV to SC infliximab in CD with perianal lesions is safe and feasible.